Upaya Meningkatkan Empati Siswa SMP Muhammadiyah 1 Malang Melalui Penggunaan Teknik Sinema Terapi - Leny Latifah; Romia Hari Susanti (JKI (Jurnal Konseling Indonesia), 2016)
Empathy is an individual reaction consisting of cognitive and affective components of the ability to understand other people's feelings. Empathy is built on the scope of awareness, so that more and more open to our own emotions, the more skilled in understanding the feelings of others. The subjects were 28 students of class VII and VIII SMP Muhammadiyah 1 Malang. The research objective increase empathy of students through the use of cinema therapy. This research is a Quasi Experiment with using the pattern of pre-test and post-test Group. The instrument used is a student empathy scale, experiment guidelines and observation guidelines. The results showed that (1) pretest of 28 students scored a minimum of 42 and maximum of 97 with a mean score of 70.4, after completing treatment therapy to improve the use of cinema empathy, posttest results indicate a minimum score of 92 and a maximum score of 151 with a mean of 120.8 , the mean difference between pretest and posttest was 50.4. (2) Based on the results of the Wilcoxon test, different values (z) after treatment with before administration of treatment is -2803, so it can be interpreted that the use of cinema therapy effective for improving empathy junior high school students.